Трудные случаи лексикографического представления слов в Толковом словаре русской разговорной речи - Sharykina, Ol’ga (Wiener Slawistischer Almanach, 2023)
The article considers difficult cases of the description of multitasking words in the Explanatory Dictionary of Everyday Russian Speech. It is commonly said that some words in the spoken variety of modern Russian have a diffuse meaning. The information about it, as a rule, is specified in the PRAGM section of the dictionary article. The special function of some adjectives in the a role of intensifiers, something which is difficult to reflect in the dictionary, is also treated.